2010
DOI: 10.1103/physrevb.82.075125
|View full text |Cite
|
Sign up to set email alerts
|

Interaction-driven topological insulators on the kagome and the decorated honeycomb lattices

Abstract: We study the spinless and spinful extended Hubbard models with repulsive interactions on the kagome and the decorated honeycomb ("star") lattice. Using Hartree-Fock mean-field theory, we show that interaction-driven insulating phases with non-trivial topological invariants (Chern number or Z2 invariant) exist for an experimentally reasonable range of parameters. These phases occur at filling fractions which involve either Dirac points or quadratic band crossing points in the non-interacting limit. We present c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
221
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(232 citation statements)
references
References 75 publications
(145 reference statements)
7
221
1
Order By: Relevance
“…However, the vanishing density of states (DOS) renders the Dirac Fermi points robust against weakly repulsive electron-electron interactions. In general, a finite interaction stength is required to open a gap at f = 1/3 and stabilize a topologically nontrivial phase [44,45]. Another topologically nontrivial band-touching occurs at the Γ-point between the upper dispersive and flat bands.…”
Section: After Fourier Transformationmentioning
confidence: 99%
“…However, the vanishing density of states (DOS) renders the Dirac Fermi points robust against weakly repulsive electron-electron interactions. In general, a finite interaction stength is required to open a gap at f = 1/3 and stabilize a topologically nontrivial phase [44,45]. Another topologically nontrivial band-touching occurs at the Γ-point between the upper dispersive and flat bands.…”
Section: After Fourier Transformationmentioning
confidence: 99%
“…19,20 It has also been found that interactions may lead to a topological insulator in a decorated honeycomb and kagome lattices. 21 The main obstacle for realizing an interaction-driven topological insulator is the required interaction profile in real space. In a honeycomb lattice, for example, this amounts to an interaction that is strongest on next-nearest-neighbor bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many-body interaction is expected to enable topological phases in strongly correlated systems by generating circulating currents and spontaneously breaking time-reversal symmetry (TRS), which act as an effective magnetic field or spin-orbit coupling [12,14,15]. This subject has attracted vigorous research due to support from mean-field studies, followed by low-energy renormalization-group analysis [13,16], and the existence of such topological phases has been suggested for the extended Hubbard model on various lattice models [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. However, unbiased numerical simulations, such as exact diagonalization (ED) and density-matrix renormalization-group (DMRG) studies, found competing states other than topological phases as the true ground states in all previously proposed systems with Dirac points [31][32][33][34] or quadratic band touching points [35,36].…”
mentioning
confidence: 99%